Pengaruh Ekstrak Biji Alpukat (Persea Americana Mill.) Terhadap Pertumbuhan Bakteri Staphylococcus Aureus Pada Luka Diabetes Metode Difusi Cakram - Nabilah Khairunnisa; Ali Napiah Nasution; Asyrun Alkhairi Lubis (STIKes Ibnu Sina Ajibarang, 2024)
. Avocado seeds are one of the plants used as a medicine for diabetes mellitus with the Latin name (Persea americana Mill.). Avocado seeds contain compounds such as alkaloids, flavonoids, saponins, tannins and triterpenoids which are beneficial for health. This study aims to determine the effect of avocado seed extract (Persea americana Mill.) on the growth of Staphylococcus aureus bacteria in diabetic wounds using the disc diffusion method. The extraction process is by maceration using 96% ethanol. The treatment was repeated 4 times with extract concentrations of 25%, 50%, 75%, 100%, as a positive control Ciprofloxacin and DMSO (Dimetyl Sulfoxide) as a negative control. The results of phytochemical screening show that avocado seeds contain alkaloids, flavonoids, saponins, tannins and triterpenoids. Based on the results of research conducted, avocado seed extract can inhibit the growth of Staphylococcus aureus bacteria as an inhibition zone is formed. The most effective concentration in inhibiting the growth of Staphylococcus aureus bacteria is at 100% concentration of 10.14 mm.